Analisis Finansial Usaha Perikanan Perahu Lampu di Desa Tumbak Kecamatan Pusomaen Kabupaten Minahasa Tenggara - Walalangi, Hizkia N.; Manoppo, Victoria E.N.; Tambani, Grace O.; Sondakh, Srie J.; Kotambunan, Olvie V. (Universitas Sam Ratulangi, 2024)
AbstractTumbak Village is one of the villages in Pusomaen District, Southeast Minahasa Regency. Most of the Tumbak villagecommunity work as fishermen. This is certainly very realistic because North Sulawesi has very large maritime resourcepotential and has coastal villages that are used as economic aspects that support the lives of the community, especiallyfishermen. One of the coastal villages that has fishermen is Tumbak Village, Pusomaen District, Southeast MinahasaRegency. The purpose of this study is to determine the profile and financial feasibility of the lamp boat fishing businessin Tumbak Village, Pusomaen District, Southeast Minahasa Regency. Based on the results of the study, it can beconcluded that the lamp boat fishermen in Tumbak Village, Pusomaen District, number 3 respondents. The ages ofthe three respondents vary, namely R1 44 years, R2 51 years and R3 55 years with elementary and junior high schooleducation levels. The average number of family dependents from the 3 respondents is 3 people. Based on the FinancialAnalysis conducted in Tumbak Village, Pusomaen District, Southeast Minahasa Regency, the lamp boat business hasan Operating Profit of Rp586,900,000, Net Profit of Rp575,394,000, Profit Rate of 890%, Benefit Cost Ratio of 9.90.Keywords: financial analysis, light boat, Tumbak VillageAbstrakDesa Tumbak merupakan salah satu desa yang ada di Kecamatan Pusomaen Kabupaten Minahasa Tenggara.Masyarakat desa tumbak sebagian besar memiliki mata pencaharian sebagai nelayan. Hal ini tentunya sangat realistiskarena Sulawesi Utara memiliki potensi sumberdaya kemaritiman yang sangat besar serta memiliki desa pantai yangdijadikan sebagai aspek ekonomi yang menunjang kehidupan masyarakat khususnya masyarakat nelayan. Salah satudesa pantai yang memiliki nelayan yaitu Desa Tumbak Kecamatan Pusomaen Kabupaten Minahasa Tenggara.Adapun tujuan penelitian ini, yaitu: mengetahui profil dan kelayakan finansial usaha nelayan usaha perahu lampu didesa Tumbak Kecamatan Pusomaen Kabupaten Minahasa Tenggara. Berdasarkan hasil penelitian maka dapatdisimpulkan bahwa nelayan perahu lampu yang ada di Desa Tumbak Kecamatan Pusomaen berjumlah 3 responden.usia dari ketiga responden berbeda-beda yaitu R1 44 tahun, R2 51 tahun dan R3 55 tahun dengan tingkat pendidikanSD dan SMP. Jumlah tanggungan keluarga dari 3 responden rata-rata adalah 3 orang. Berdasarkan Analisis Finansialyang dilakukan di Desa Tumbak Kecamatan Pusomaen Kabupaten Minahasa Tenggara, usaha perahu lampu memilikiOperating Profit sebesar Rp586.900.000, Net Profit sebesar Rp575.394.000, Profit Rate sebesar 890%, Benefit CostRatio 9,90.Kata kunci: analisis finansial, perahu lampu, Desa Tumbak